Modeling Pospay and Multi-Lane Free Flow Integration for Revenue Increase - Krisnawanti, Krisnawanti; Fathurahman, Dimas Mukhlis; Haryaman, Adang; Sulaeman, Muhammad Rifqi; Pratama, Rapi Sukma (Program Pascasarjana Magister Teknik Industri Universitas Mercu Buana, 2024)
The rise of e-commerce in Indonesia has made digital payment systems increasingly important. One such system is PT. Pos Indonesia’s Pospay application. However, the app is not very popular among users as indicated by its low download numbers and ratings. To address this issue, the potential benefits of combining the Pospay application with Cantas to facilitate toll road transactions were examined. The aim was to increase public awareness of the Pospay application, which would lead to increased revenue. A dynamic system approach was used to develop an optimal strategy for improving Pospay services in the Public Transport sector and integrating it as a toll payment method in the MLFF (Multi-Lane Free Flow) system. The initial dynamic system modeling, using a Causal Loop Diagram (CLD), revealed that service innovation, customer satisfaction, and company revenue are interrelated variables that influence each other. The results of this research can be used as suggestions for companies in developing service innovation strategies.